Analisis Kultur Sekolah di SD Negeri Sumowono Kaligesing Purworejo - Zulfa Syafiya (Fakultas Ilmu Pendidikan, 2025)
This research aims to analyze school culture and analyze the supporting and inhibiting factors of school culture at Sumowono Kaligesing Elementary School, Purworejo. This study is a qualitative descriptive study with the principal, teachers, and students selected through purposive sampling as informants. Data were collected through interviews, observation, and documentation. Then, it was analyzed using data collection techniques, data condensation, data presentation, and conclusion drawing. The results of the study indicate that the school culture at Sumowono Elementary School supports learning. Physical artifacts at Sumowono Elementary School have supported the learning process, but there are several spaces that require maintenance and repair. Non-physical artifacts are embedded through interactions and behaviors. The assumption of the school community is that acculturation is the commitment of the school community to reflect practices that support a positive school culture. Supporting factors are the school's vision and mission, the principal's leadership, and relationships with the school community. Meanwhile, inhibiting factors are poorly maintained facilities and infrastructure, limited human resources, incompatibility of values/culture, and lack of evaluation and supervision.